Economic analysis of FDG‐PET–guided management of the neck after primary chemoradiotherapy for node‐positive head and neck squamous cell carcinoma1. Issue 9 (18th September 2012) - Pryor, David I.; Porceddu, Sandro V.; Scuffham, Paul A.; Whitty, Jennifer A.; Thomas, Paul A.; Burmeister, Bryan H.
Abstract Background The aim of this economic analysis was to model different strategies using pre‐treatment nodal stage or nodal response assessment with CT or positron emission tomography (PET)/CT to determine the need for neck dissection. Methods A cost‐minimization analysis was developed on the basis of probability data from a prospective study of PET‐guided management of the neck in patients achieving a complete response at the primary site. Costs were derived from our institution's activity‐based clinical costing system. The effect of uncertainty was tested with sensitivity and scenario analyses including nationally representative cost data. Results Strategies incorporating PET had a 7% rate for neck dissection compared with 44% for CT‐guided and 90% for planned neck dissection. The cost per patient was A$16, 502 for planned neck dissection, A$8014 for CT‐guided, and A$2573 for PET‐guided. A policy with PET used only for incomplete response on CT was the least‐cost strategy (A$2111). Policies incorporating PET remained the most efficient for all sensitivity/scenario analyses. Conclusion The incorporation of PET/CT into nodal response assessment significantly reduced the number of unnecessary neck dissections and generated considerable cost savings in our cohort. © 2012 Wiley Periodicals, Inc. Head Neck, 2013